URGENSI KEBERADAAN KOTA-KOTA PESISIR TERHADAP KAJIAN SEJARAH MARITIM DI NUSANTARA: SEBUAH STUDI STRUKTURALISME - Mochammad Nginwanun Likullil Mahamid (Handep: Jurnal Sejarah dan Budaya, 2023)
This article aims to review the existence of coastal cities based on structuralism theory to understand the urgency of studying maritime history in the archipelago. The archipelago has a vast ocean expanse that allows interaction between individuals in maritime activities, namely shipping, and trade. On the other hand, it also had consequences; the arrival of foreigners to the archipelago significantly impacted maritime conditions, especially in forming coastal city structures and several other supporting elements. The study used the historical method. The stages were heuristics, source criticism, interpretation, and historiography. Of all these things, this article discusses three structuralism ideas by Fernand Braundel and their relations to studying maritime history in the archipelago, including longue durée, conjoncture, and evenementiel.